Significados de familia en personas con orientación homosexual en la ciudad de Bogota (2022)
The present research work was conducted under a systemic perspective, qualitative with narrative design, which aims to analyze the meanings of family in people with homosexual orientation in the city of Bogotá. D.C. Four people of different ages and occupations, people with homosexual orientation, participated in the study. The meanings of family in homosexual persons were obtained through a free and open interview and analyzed by 3 categories: Meanings attributed to the functions of the family, where the similarity in these meanings and the family perspective of each interviewee were analyzed. Meanings assigned to the different roles played within the family, in this category, the different roles played in a family were analyzed, such as the role or ideal of being a good father and a good mother, the ideal of being a good sibling7a and, finally, the ideal or role of being a good daughter/daughter